Untargeted Metabolomics Reveals Alterations in the Primary Metabolites and Potential Pathways in the Vegetative Growth of Morchella sextelata - Deng, Kejun; Lan, Xiuhua; Fang, Qing; Li, Mengke; Xie, Guangbo; Xie, Liyuan (Frontiers in Molecular Biosciences, 2021)
Morchella sextelata is one of the true morels, which have recently been artificially cultivated and stable production in China. Analysis of the changes in metabolites during the developmental stages of M. sextelata is important to understand the underlying changes of primary metabolites. It may also provide valuable information for the cultivation efficiency of M. sextelata. In this study, mass spectrometry-based untargeted metabolomics was used to analyze the alteration of metabolites during the developmental stages of M. sextelata. Three developmental stages were categorized based on morphological changes, including the young mushroom period, marketable mature period, and physiological maturity period. The result showed that the changes in the content of metabolites involved in the different growth stages were different. The relative contents of Linoleic acid, mannitol, oleamide, and betaine were higher. Flavor substances were significantly metabolizable during commodity maturity, while amino acids, organic acids, and lipids were significantly metabolizing at physiological maturity. MetaboAnalyst showed that the metabolic pathways with significant changes included those related to the following: Pyrimidine metabolism, Vitamin B6 metabolism, Arginine biosynthesis, Lysine biosynthesis, and Lysine degradation. The results can provide a theoretical basis for further clarifying the metabolic regulation mechanism and lay the foundation for special-nutrition breeding of M. sextelata.